2018
DOI: 10.1002/lno.11042
|View full text |Cite
|
Sign up to set email alerts
|

Environmental determinants of larval herring (Clupea harengus) abundance and distribution in the western Baltic Sea

Abstract: The analysis of the abundance and distribution of the early life‐history stages of the western Baltic spring‐spawning herring population, spanning 23 yr, revealed that the abundance of yolk‐sac larvae was strongly spatially structured and significantly more abundant during the optimal temperature window for viable hatch of herring larvae (9°C to 13°C). The percentage of time encompassing this optimal temperature window exhibited a major contraction between 1995 and 2000 that may have contributed to reducing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
12
2
Order By: Relevance
“…Nonetheless, the temperature range in Dodson et al . (2019) was much larger (5–20°C) than in the present study (4–8°C). The analyses presented here showed that the effect of zooplankton on the relative stage occurrence is only significant when temperature is above a certain level (>6°C).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Nonetheless, the temperature range in Dodson et al . (2019) was much larger (5–20°C) than in the present study (4–8°C). The analyses presented here showed that the effect of zooplankton on the relative stage occurrence is only significant when temperature is above a certain level (>6°C).…”
Section: Discussioncontrasting
confidence: 81%
“…Grey points represent stations with five or less 1d and 2a larvae in total found a greater positive relationship between abundance of yolk-sac larvae and preflexion larvae for western Baltic spring spawning herring at low range of temperatures indicating higher mortality during the transition at higher temperatures. Nonetheless, the temperature range inDodson et al (2019) was much larger (5-20 C) than in the present study (4-8 C). The analyses presented here showed that the effect of zooplankton on the relative stage occurrence is only significant when temperature is above a certain level (>6 C).…”
contrasting
confidence: 80%
See 1 more Smart Citation
“…Therefore, significant export of larvae by current regimes was considered negligible. According to literature on the temperature-dependent duration of yolk consumption (Klinkhardt, 1986) all larvae within a total length range of 5-9 mm were considered hatchlings in the yolk-sac stage (Polte et al, 2017;Dodson et al, 2019). For this study, seasonal shifts of (i) peak hatching and (ii) hatching duration were investigated, based on the occurrence of maximum abundance of yolk-sac larvae and the number of days where yolk-sac larvae could be found in the system.…”
Section: Timing Of Larval Hatchmentioning
confidence: 99%
“…Temperature affects recruitment success, as shown by case studies in the Baltic Sea (Baumann et al, 2006;Cardinale et al, 2009;Dodson et al, 2018;Köster et al, 2005), Barents Sea (Gjøsaeter & Bogstad, 1998;Ottersen & Loeng, 2000), North Sea stocks (Arnott & Ruxton, 2002;Kempf, Floeter, & Temming, 2009;van der Veer, Pihl, & Bergman, 1990), on Atlantic cod (Kempf et al, 2009;Olsen et al, 2010;Planque & Fox, 1998;Planque & Frédou, 1999) and flatfish stocks (Fox, Planque, & Darby, 2000;Henderson & Seaby, 2005;Nash & Geffen, 2000;Rijnsdorp et al, 1992); mechanistic link through food availability in the North Sea (Beaugrand et al, 2003;Payne et al, 2009)…”
Section: Variables Indices Hypothesesmentioning
confidence: 95%